Consumer satisfaction analysis towards chocolate-based product using importance performance analysis and customer satisfaction index method: Case study at Kampung Coklat Blitar Indonesia - Septifani, Riska; Mustaniroh, Siti Asmaul; Rahmatri, Dio (Journal of Management, Economics, and Industrial Organization, 2019)
Chocolate is a base product made from cacao-bean and cacao-fat. Chocolate industry in Indonesia has much improved. Indonesia has many cacao producer that produce many kinds of chocolate-based products, whether in industrial or home-industry scale. One of the chocolate-based product is Kampung Coklat Blitar. There are several chocolate-based products produced by Kampung Coklat Blitar. The aim of this research is about to find out all of the attributes that should be improved towards chocolate-based products in Kampung Coklat Blitar, using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) method. The data was collected from 120 respondents, who were customers of Kampung Coklat Blitar. 16 attributes were analyzed in this research. Calculation result using IPA method showed that attributes categorized into quadrant I (concentrate here) or main priority for improvement are size and volume, and also price. Attributes that are categorized into quadrant II (keep up the good work) or attributes that need to be maintained are taste, condition of raw material, expiration date information, and product durability. Attributes that are categorized into quadrant III (low priority) or second priority for improvement are nutrition facts, form, convenience to complaint, advertisement and promotion, product packaging, brand popularity, and product information. Lastly, attributes that are categorized into quadrant IV are variation, benefit, and content of preservative. Calculation result using CSI method showed that the CSI value or consumer satisfaction level is 75%. This value is in the range of 0,66 – 0,80, which means that consumers are satisfied with chocolate-based products produced by Kampung Coklat Blitar.